(untitled) (Global Journal of Human-Social Science, 2013)
In India the solid waste increasing rapidly day by day due to increasing the living standards of human beings by leaps & bounds in India approximately last twenty years and due to increasing population. The handling of solid waste in India is not up to the mark. We always consider that it is a total waste thing, but if we reduce, reuse or recycle it becomes a very useful thing. The poor handling of solid waste cause of increases the pollution, human beings health, Rising global temperatures, animals, and many types of ecosystems and bad effect on environment. In this paper we describe that solid waste handling is not a single man work; it is the sole responsibility of all the human beings to maintain the balance of the ecosystem by proper handling the solid wastes. In this paper we also describe that the role of human being to reduce the solid waste and government of India.